Implementation of Curriculum Strategies For Medical Education - Betelmal, Ibrahim; Alnasfi, Suad (Benghazi University Medical Journal, 2024)
In a world where medical knowledge is expanding, how we teach physicians is as important as what we teach. An integrated curriculum can bridge basic sciences and clinical practice and help develop soft skills such as critical thinking. By integrating disciplines, we prepare future doctors to address the challenges of modern healthcare systems.